Musical influences and their aesthetic indicators in the theatrical Iraqi show (o body. Talk) as a pattern - شيماء حسين طاهر أ. م. د (lark, 2021)
The musical influence is an important element in the process of receiving because of its implications. It is an important element that reveals the general atmosphere and in a semantic, aesthetic and indicative center that supports the presentation. The first chapter included (the theoretical framework) and included the research problem represented by the following question (Where do the aesthetics of the musical influence lie in the presentation and what is its significance? The aesthetic in the Iraqi theatrical performance), and the importance of the research included shedding light on the musical influence as an aesthetic sign that has various connotations in the theatrical performance system. The aim of the research is to identify the musical influence in the Iraqi theatrical performance and the mechanisms of its operation as an aesthetic sign that contributes to the taste of the show and its interpretation. The research was concluded with definitions, and the second chapter included two topics, the first section included musical influences as an aesthetic mediator, while the second topic included the musical influence as a psychological aesthetic mediator. The second chapter concluded with the indicators that resulted from the theoretical framework. The third chapter is devoted (research procedures) and the indicators that resulted from the theoretical framework as a tool for analysis within a descriptive (analytical) approach and scenes of performances and photographs to come to the analysis of the presentation (Remember, O Body) directed by (Mohamed Muayyad) in (2010). And in an intentional way for reasons justified by the researcher to keep pace with the investigations and to achieve the objectives of the research and solve a problem. The fourth chapter concluded a number of results, the most important of which are: • The musical influencer turns into a sign that transmits its code through kinetic performance • The musical influence turns into a signal system that reduces language Then conclude with a summary of the search words.